Penerapan Sistem Informasi Manajemen dalam Meningkatkan Kualitas Pelayanan Konsumen UMKM Songket Unggan - Putri, Okta Sari Heppy; SY, Muhtarrom Naufal; Kumbara, Vicky Brama (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of Management Information Systems (MIS) in improving service quality for consumers at Songket Unggan MSMEs in Sijunjung Regency, West Sumatra. The research employs a descriptive qualitative approach to gain an in-depth understanding of MIS implementation within the enterprise. Data were collected through in-depth interviews with business owners and consumers, direct observation of service and operational processes, and documentation of transaction records and digital promotional media. Data analysis was conducted through data reduction, data display, and systematic conclusion drawing to obtain a comprehensive overview of the effectiveness of information system implementation in enhancing service quality. The results indicate that the adoption of digital transaction recording, social media promotion, and non-cash payment systems has improved service speed, transaction accuracy, and customer satisfaction. However, the implementation still faces challenges related to limited digital literacy and supporting infrastructure. Therefore, improving digital competencies and strengthening local government support are essential to optimize MIS implementation.